LEGAL VIEWS OF THE CORPORATE INCOME TAX PROVISION. - Walgenbach, Paul H. (The Accounting Review, 1959)
Abstract Since the emergence of the tax allocation views of the Committee on Accounting Procedure of the American Institute of Certified Public Accountants and the lengthy and well-documented excoriation of the allocation proposition by the U.S. Securities and Exchange Commission (SEC) in Accounting Series Release No. 53, a good deal of attention in accounting literature has been given to the role of the corporate income tax provision in income determination. Despite the fact that tax allocation procedures have found a large measure of acceptance in practice and although the position of SEC has changed extensively, there remains considerable difference of opinion with respect to the basic nature of the tax deduction and how it should be viewed from the standpoint of income determination, statement presentation and disclosure, rate regulation, and financial analysis. Since the inception of corporate income taxes in the U.S., the legal view of the tax provision has frequently been a rather cursory one, and in practically every case the provision has been regarded in the nature of cost or expense.